2014
DOI: 10.1371/journal.pone.0108646
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Basic Protein Induces Neuron-Specific Toxicity by Directly Damaging the Neuronal Plasma Membrane

Abstract: The central nervous system (CNS) insults may cause massive demyelination and lead to the release of myelin-associated proteins including its major component myelin basic protein (MBP). MBP is reported to induce glial activation but its effect on neurons is still little known. Here we found that MBP specifically bound to the extracellular surface of the neuronal plasma membrane and induced neurotoxicity in vitro. This effect of MBP on neurons was basicity-dependent because the binding was blocked by acidic lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 85 publications
3
31
0
Order By: Relevance
“…However, in chronic EAE sections MBP accumulated also around neuronal cells, such as Purkinje cells, as can be seen in sections Figure 4 E and F. Indeed, it was recently shown that MBP binding may induce neuron-specific toxicity by direct damaging the neuronal plasma membrane integrity. 41 Consistent with this, our results indicate that following demyelination, new MBP aggregates may damage neuronal cells by a prion-like mechanism. 42 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, in chronic EAE sections MBP accumulated also around neuronal cells, such as Purkinje cells, as can be seen in sections Figure 4 E and F. Indeed, it was recently shown that MBP binding may induce neuron-specific toxicity by direct damaging the neuronal plasma membrane integrity. 41 Consistent with this, our results indicate that following demyelination, new MBP aggregates may damage neuronal cells by a prion-like mechanism. 42 …”
Section: Resultssupporting
confidence: 90%
“… 19 In the brains of mice suffering from chronic EAE, it can be the reduced levels of cholesterol and other lipids which may preclude the entrance of MBP to its appropriate location in the myelin sheath and induce its aggregation outside the membrane. Outside the membrane, aggregated MBP may damage neighboring neurons, 41 promoting further neurodegeneration. It remains to be established whether changes in lipid composition result or encourage the demyelinating process.…”
Section: Discussionmentioning
confidence: 99%
“…MBP displays direct neuron-specific (but not glial) toxicity in vitro, which seems to depend on its binding to sialic acid-containing lipids on the neuronal surface and regulation of the nonselective cation flow [79, 80]. Both in the presence and absence of T cells, IS MBP84-104 induces IL-6 and spinal Ca 2+ signaling [10].…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of lipid components in APP proteolytic processing has been extensively reviewed ( 100 ); Aβ production is modulated by sphingolipids. Demyelination leads to a release of myelin proteins ( 101 ): Nogo, myelin-associated glycoprotein, and oligodendrocyte myelin glycoprotein inhibit neuronal regeneration via Nogo and PirB receptors ( 102 , 103 ), and MBP causes damage since it acts directly on the neuronal membrane ( 104 ). This protein, which has been regarded as one of the antigens for MS, performs many functions: it is involved in Aβ aggregation and inhibits Aβ fibril assembly ( 105 ), which affects Aβ levels.…”
Section: Proteins Involved In App Proteolytic Processing In Demyelinamentioning
confidence: 99%